Analisis SWOT dalam Perencanaan MUK pada Sistem Agroforestri berbasis Tumpang Sari Vanili dan Kopi di PT Inhutani I Umha Pimping - Mar Atussha Lihah (Jurnal Wana Tropika, 2025)
This study aims to assess Multi Forestry Business (MUK) planning in the agroforestry system at PT Inhutani UMHA Pimping located in Bulungan, North Kalimantan. MUK is a forest management strategy that combines various business sectors, including agriculture and ecotourism, to maximize the potential of natural resources and improve the welfare of the surrounding community. Thus, PT Inhutani plans to implement an agroforestry system based on intercropping between vanilla and coffee plants. These two commodities were chosen because of their suitability to the tropical climate and the potential for high selling prices in local and export markets. This research used a descriptive qualitative method based on a case study in the PT Inhutani I UMHA Pimping area and data sources were obtained by observation, interviews and literature studies. This research also identifies strategies that can be applied to overcome weaknesses and take advantage of existing opportunities. The results of the SWOT analysis show that PT Inhutani has great potential to develop agroforestry businesses, but successful implementation depends on the ability of managers to overcome threats such as pest attacks and market price fluctuations. Therefore, it is important to conduct intensive training for farmers and build infrastructure that supports the development of ecotourism. Thus, this research is expected to contribute to the development of sustainable forest management strategies and increase state revenue from the agricultural sector which is currently still relatively low